Multiple session mesotherapy for management of coxofemoral osteoarthritis pain in 10 working dogs: A case series - Alves, João C.; Santos, Ana; Jorge, Patrícia; Lafuente, Pilar (Canadian Veterinary Journal, 2023)
The aim of this study was to document the effects of mesotherapy in working dogs diagnosed with hip osteoarthritis (OA) and related pain. Ten police working dogs with hip OA and related pain were treated with a combination of lidocaine, piroxicam, and thiocolchicoside, injected in multiple intradermal points. Seven treatment sessions were conducted. The Canine Brief Pain Inventory (CBPI) and the Hudson Visual Analogue Scale (HVAS) were used in the assessment of response to treatment compared to evaluation before treatment (TO), after 15 d, 30 d, 60 d, 90 d, 120 d, 150 d, and 180 d after initial treatment. Results were compared using the Wilcoxon signed-rank test. Significant differences were experienced in CBPI scores comparing moments with TO: at 15 d (P = 0.03 for Pain Interference Score - PIS) and P = 0.02 for Pain Severity Score - PSS), 30 d (P < 0.05 for PIS and P < 0.05 for PSS), 60 d (P = 0.04 for PIS and P = 0.01 for PSS) and 180 d (P = 0.04 for PSS). Individual treatment results were considered successful in 40% of animals at 15 d and 30 d, 66.7% at 60 d, 44% at 90 d, 37.5% at 120 d, and 25% at 150 d. The HVAS scores showed no significant differences. Mesotherapy may be an option for the treatment of canine musculoskeletal-related pain. Further studies are required.
Mésothérapie en plusieurs séances pour la prise en charge de la douleur arthrosique coxofémorale chez 10 chiens de travail : une série de cas]
Keywords: animals; dog diseases; dogs; mesotherapy; musculoskeletal pain; osteoarthritis; pain measurement; working dogs; Scopus; JCR